Study on constitutive model of marine soft soil based on disturbed state concept - Heng Zhang; Yindong Sun; Yajun Liu; Ke Wu; Yang Zheng; Haijun Lu; Rong Chen (Scientific Reports)
Abstract Marine soft soils are widely distributed in near-coastal areas and pose significant risks to the stability of structures due to their unique mechanical properties. While researchers worldwide have used various theoretical constitutive models and scientific methods to investigate the mechanical properties of marine soft soils, no attempts have been made to establish a mechanical model based on the concept of disturbed state for marine soft soils. In this paper, based on the concept of disturbed state, we utilize triaxial and creep test methods, apply the Duncan tensor modulus to describe the relatively complete state of marine soft soil, and modify the Cambridge model to characterize the fully adjusted state. Additionally, we derive the disturbance function to establish the intrinsic model for the disturbed state of marine soft soil. The model’s accuracy is verified by comparing its predictions with experimental test results. Subsequently, the model is applied to engineering cases and compared with numerical simulation results. The study shows that the results from the disturbed state constitutive model are consistent with the experimental data and can effectively be used to assess the foundation bearing capacity of marine soft soil layers. The development of the constitutive model based on the concept of disturbed state offers a new theoretical framework and calculation method for studying the mechanical properties of marine soft soil in near-coastal regions.